EXPLORING PREDICTORS OF EXECUTIVE FUNCTION SKILLS OF KINDERGARTEN LEARNERS: PREDICTORS OF EXECUTIVE FUNCTION SKILLS OF KINDERGARTEN LEARNERS - Batiancila, Maricel F.; Gevana, Daisy R.; Salado, Jean M.; Opingo, Kaitlin Marie M.; Padillo, Gengen G.; Manguilimotan, Ramil P.; Peteros, Emerson D.; Capuno, Reylan G. (International Journal of Social and Management Studies, 2025)
This research assessed the executive function skills of kindergarten learners at the identified schools in Lapu-Lapu City Division for the school year 2021-2022 as a basis for the Executive Function Skills Development Plans. A descriptive-correlational method of research was utilized in determining the level of manifestation of executive function skills of 290 kindergarten who were selected using random sampling. An adapted survey questionnaire was used to collect the data, which were analyzed using frequency counts, percentages, weighted means, and multiple regression. Findings revealed that the majority of the learners were aged 6 years old, with an equal distribution of female and male respondents, most parents having graduated from high school, 1-2 siblings, and a combined family monthly income of 10,000 pesos or below. Regarding learners’ executive function skills, results showed that doing homework, organizing materials, handling long-term projects, and remembering were at the manifested level, while problem-solving and self-control were at a less manifested level, with the overall level of executive function skills at the manifested level. The results further showed that only the combined monthly income of the profile has a significant relationship with the learners' executive function skills. It is recommended that the executive function skills development plan be implemented in each research locale.